1992
DOI: 10.1007/bf02253581
|View full text |Cite
|
Sign up to set email alerts
|

Do autoreceptors mediate dopamine agonist — induced yawning and suppression of exploration? A critical review

Abstract: The hypothesis that stimulation of dopamine autoreceptors is the mechanism by which dopamine agonists induce yawning and suppression of exploration is critically examined. It is shown that the relation between reduced extracellular dopamine levels, assessed by microdialysis, and behavioural effects of dopamine agonists, a dopamine synthesis inhibitor and a granule storage blocker is highly inconsistent. The time-course and duration of the behavioural effects of dopamine agonists differ from the reduction of ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
1

Year Published

1993
1993
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(29 citation statements)
references
References 93 publications
0
28
1
Order By: Relevance
“…The existence of behaviourally inhibitory postsynaptic "D 2 like" receptors has been proposed in behavioural studies before (Costall et al, 1981;Rubinstein et al, 1988, for review see Sffthle, 1992). The data presented here suggest that the D 3 receptor may be the target.…”
Section: Discussionmentioning
confidence: 79%
“…The existence of behaviourally inhibitory postsynaptic "D 2 like" receptors has been proposed in behavioural studies before (Costall et al, 1981;Rubinstein et al, 1988, for review see Sffthle, 1992). The data presented here suggest that the D 3 receptor may be the target.…”
Section: Discussionmentioning
confidence: 79%
“…Quinpirole, and other direct and indirect dopamine receptor agonists, decrease locomotor activity at low doses. This suppressive effect has been interpreted as the behavioral consequence of activation of a dopamine autoreceptor, which results in a decrease in dopamine synthesis and/ or release, although this hypothesis is not universally accepted [Stahle, 1992] [Accili et al, 1996]. D 3 null mutant mice developed by Xu et al [1997] showed a different phenotype, and were only transiently more active than wild-type mice, an effect not associated with anxiety state.…”
Section: Discussionmentioning
confidence: 94%
“…This contention is consonant with the decrease in mesolimbic DA activity in nicotine withdrawal reported in the present and previous (Hildebrand et al 1998) studies from our laboratory. Other data, however, report a lack of correlation between changes in NAC DA output and yawning behavior elicited by DA agonists, DA synthesis inhibitors, or DA storage blockers (Ståhle 1987(Ståhle , 1992. In these studies, however, the experiments were performed almost immediately following implantation of the microdialysis probe and changes in extracellular DA may well have been blunted by the acute tissue trauma (Westerink 1995).…”
Section: Discussionmentioning
confidence: 98%